IKLAN : PRODUK BUDAYA POP YANG MENELIKUNG PEREMPUAN - Perwita, Alvika Hening (KOMUNITAS)
Series of ads that appear in printed media, electronic, and internet diverse increasingly  and  of  course  we  can  not  deny  its  existence.  Most  of  the advertising icon is  using the  profile of women as  an object.  Even  women icon  sometimes  is  displayed  only  and  no  links/  anything  to  do  with  the product  being  advertised.  Overall  the  product  ads  directly  related  to women  are  aimed  to  attract  attention,  exploit  the  female  body,  degrade women,  and  even  provide  examples  of  sexual  harassment.  Besides  those cases,  women  also  made  the  largest  consumer  advertising  products.  And the  most  pitiful  representation  of  women  in  the  ads,  which  portrayals  of women in  the  ads are  always,  sought perfection and  automatically it  will present  camouflage  to  the  real  world  of  women.  The  fact  that  popular culture  products  capable  of  twisted  woman  was  already  familiar  to  the public. Therefore, we require a study that could uphold women. There was a  study  which  until  now  has  not  been  reviewed  by  a  group  of  feminism, which is about the strength of women. This study said that woman must be held to prove that she was able to exist in the lives of men and the growing popular culture products.